"I had never been at home in the world"1: A case for Black-Indigenism. Issue 1 (1st January 2019) - Limes-Taylor Henderson, Kelly
Abstract: In this article, I argue that the Black experience in the United States settler colony is one primarily based in a systematic erasure of indigeneity from the enslaved African. Understanding the Black condition as a manifestation of White America's historical response to indigeneity, I consider the marginalized perspectives of Black decolonization work that has pushed and continues to push back against the centuries-long history of settler colonialism in the region known as North America. Placing Black and Indigenous decolonizing histories and practices in conversation with each other is part of what I call Black-Indigenism and is inspired by the work of Sylvia Wynter. Wynter and others recognize Blackness as an integral factor in the argument for Indigenism that informs and furthers the aims of Indigenist and Indigenous decolonization educative work and movements.